FROM ALGORITHMS TO JUSTICE: A CRITICAL LITERATURE REVIEW OF THE IMPACT OF ARTIFICIAL INTELLIGENCE ON HUMAN RIGHTS AND THE URGENCY OF SPECIFIC REGULATION IN INDONESIA - Gunawan Widjaja (ADISAM Publisher, 2026)
The rapid development of artificial intelligence (AI) has transformed the landscape of automated decision-making across various sectors, yet it also poses serious risks to human rights through algorithmic bias, privacy violations, and the erosion of individual autonomy. This article examines the multidimensional impact of AI on human rights. The research findings underscore the need for regulations that integrate algorithmic transparency, human oversight, and developer accountability to protect vulnerable groups. Policy recommendations include the establishment of an independent AI oversight body, national digital literacy training, and the harmonisation of global standards to position Indonesia as a responsible AI leader in ASEAN. This study contributes to the discourse on digital human rights by offering a conceptual framework for the transition from a technology-centric to a human rights-centric paradigm in Indonesia’s AI governance.